2013
DOI: 10.1111/rssc.12037
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing from Unrepresentative Experiments: A Stratified Propensity Score Approach

Abstract: The paper addresses means of generalizing from an experiment based on a nonprobability sample to a population of interest and to subpopulations of interest, where information is available about relevant covariates in the whole population. Using stratification based on propensity score matching with an external populationwide data set, an estimator of the population average treatment effect is constructed. An example is presented in which the applicability of a major education intervention in a non-probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 24 publications
0
78
0
Order By: Relevance
“…There is a growing appreciation that, rather than being restricted to convenience samples that often exclude harder-to-recruit socio-economic groups, research studies should strive to increase the diversity of their samples (Keiding and Louis, 2016). Consistent with this aim of achieving greater “external validity” for both experimental and observational study findings, there is a growing body of statistical literature and methods that aim to maximize the population representativeness even when study conditions do not permit a full application of traditional probability sampling methods (see Dugoff et al 2014; O’Muircheartaigh and Hodges, 2014; Stuart et al, 2015; Elliott and Valliant, 2017). While there now exists institutional commitment to ensuring sex differences are incorporated into study designs (https://grants.nih.gov/grants/guide/notice-files/NOT-OD-15–102.html) the same is not yet true for other factors such as race and ethnicity, SES and urbanicity.…”
Section: Adolescent Diversity and National Representativenessmentioning
confidence: 99%
“…There is a growing appreciation that, rather than being restricted to convenience samples that often exclude harder-to-recruit socio-economic groups, research studies should strive to increase the diversity of their samples (Keiding and Louis, 2016). Consistent with this aim of achieving greater “external validity” for both experimental and observational study findings, there is a growing body of statistical literature and methods that aim to maximize the population representativeness even when study conditions do not permit a full application of traditional probability sampling methods (see Dugoff et al 2014; O’Muircheartaigh and Hodges, 2014; Stuart et al, 2015; Elliott and Valliant, 2017). While there now exists institutional commitment to ensuring sex differences are incorporated into study designs (https://grants.nih.gov/grants/guide/notice-files/NOT-OD-15–102.html) the same is not yet true for other factors such as race and ethnicity, SES and urbanicity.…”
Section: Adolescent Diversity and National Representativenessmentioning
confidence: 99%
“…In addition, the topic of external validity has not been discussed as much in the social and behavioral sciences (with a few recent exceptions, including Olsen et al, 2013; O’Muircheartaigh & Hedges, 2014; Tipton, 2013). Some of the considerations may be quite different in different fields.…”
Section: Issues Associated With Representativeness In Randomized Trialsmentioning
confidence: 99%
“…After a study has concluded, generalizability can still be assessed through the use of propensity score‐based subclassification approaches such as that developed by O'Muircheartaigh and Hedges () and as we demonstrated in this paper. An advantage of this approach is that it only requires data sufficient to estimate a propensity model of study participation.…”
Section: Resultsmentioning
confidence: 90%
“…We demonstrate how this question can be addressed using a propensity score‐based poststratification approach developed by O'Muircheartaigh and Hedges () to estimate population average treatment effects from studies involving nonrepresentative samples. We apply this method to data from the Flexibility in Duty Hour Requirements for Surgical Trainees Trial (“FIRST Trial”) to estimate the average effect of a resident duty hour policy change in the population of general surgery residency programs and affiliated hospitals (of which the FIRST Trial sample was a subset) and the subset of the inference population that did not participate in the FIRST Trial.…”
Section: Introductionmentioning
confidence: 99%